Associations of endocrine-disrupting chemicals mixtures with serum lipid and glucose metabolism among overweight/obese and normal-weight children: A panel study - Yuanyuan Zhang; Biao Zhang; Huihua Yang; Miao Liu; Jie Wang; Lei Zhao; Wenting Guo; Meng Li; Xuefeng Lai; Liangle Yang; Xiao Meng; Cuijuan Wang; et al. (Ecotoxicology and Environmental Safety)
Background: Endocrine-disrupting chemicals (EDCs) can disturb lipid and glucose metabolism, but few studies have explored the effects of EDC mixtures and underlying inflammation mechanisms in weight-specific children. Methods: We conducted a panel study with 3 repeated visits among 144 children aged 4–12 years. For each visit, participants provided morning urine samples for 4 consecutive days and fasting blood samples on day 4. A total of 36 EDCs were measured, including 10 per- and polyfluoroalkyl substances (PFAS), 3 phenols, 3 parabens, 10 phthalates, and 10 polycyclic aromatic hydrocarbons. We used quantile g-computation, grouped weighted quantile sum (GWQS) regression, and linear mixed-effect models to evaluate and validate the associations of the mixture and individual effects of EDCs on lipid and fasting blood glucose (FBG). Further, mediation models were applied to explore the potential role of cytokines in the relationships of EDCs and outcomes. Results: A quantile increase in EDC mixtures was associated with elevated triglyceride (TG) (β = 0.18, 95 % CI: 0.04, 0.33) and FBG (β = 0.02, 95 % CI: 0.01, 0.04). Also, GWQS regression revealed that PFAS contributed the most to the overall effects for TG and FBG, followed by phenols. These associations were more pronounced in overweight/obese children. Regarding individual pollutants, we observed positive relationships of several PFAS with TG and FBG. Furthermore, chemokine ligand 2 mediated the associations of PFAS with TG among overweight/obese children. Conclusions: The present study suggested that the EDC mixtures were associated with elevated lipid and glucose levels among children, particularly for those with overweight/obesity.